2019
DOI: 10.4103/jhrs.jhrs_149_18
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Anti-Müllerian hormone cutoff for diagnosis of polycystic ovarian syndrome in women of reproductive age-bearing Indian ethnicity using the automated Anti-Müllerian hormone assay

Abstract: Context: Polycystic ovary syndrome diagnosed by Rotterdam criteria, is the most common cause of anovulatory infertility. The criteria of polycystic ovarian morphology (PCOM) are subject to operator variability and technological advances. Serum anti-Müllerian hormone (AMH) level has been proposed as a more reliable alternative to antral follicle count. There is a paucity of data on use of AMH for diagnosis of PCOS in Indian women. Aim and Objectives: The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Similar to our study Swanton et al 11 found that significantly higher number of retrieved oocyte in PCO group in IVF or ICSI cycle. Mahajan et al 23 also found that the mean number of total oocytes retrieved in PCOD (23.03 ± 9.9) were significantly higher as compare to control group (10.39 ± 6.03) and mean number of matured oocytes were significantly higher (P< 0.05) in PCOD (18.51 ± 8.99) than the controls (8.3 ± 4.78). This higher number of total oocyte retrieval and matured oocyte is probably because the AMH level in patients with PCOS is not only related to increase in the follicle pool but also increase in the production per follicle.…”
Section: Discussionmentioning
confidence: 88%
“…Similar to our study Swanton et al 11 found that significantly higher number of retrieved oocyte in PCO group in IVF or ICSI cycle. Mahajan et al 23 also found that the mean number of total oocytes retrieved in PCOD (23.03 ± 9.9) were significantly higher as compare to control group (10.39 ± 6.03) and mean number of matured oocytes were significantly higher (P< 0.05) in PCOD (18.51 ± 8.99) than the controls (8.3 ± 4.78). This higher number of total oocyte retrieval and matured oocyte is probably because the AMH level in patients with PCOS is not only related to increase in the follicle pool but also increase in the production per follicle.…”
Section: Discussionmentioning
confidence: 88%